(3GdbjGS GdGbJUGOj (B:s (3GdfXQjI h GdJMdjd (B/s - (3GdaJdGhj, cGed YdGhj cGXes; (3GdRHjOj, MSf dWja s ((3YeGf(B: s (3OGQ UaGA(B, s, 2011)
(3fWGb GdbjGS GdGbJUGOj h WHjYJg h fehPL GdGfMOGQ GdNWj Pj GdeJZjQjf h GdGfMOGQ GdNWj GdeJYOO , GdGfMOGQ h JMdjd GdJHGjf , eTcdI GdGQJHGW GdPGJj h eTcdI GdGQJHGW GdNWj GdeJYOO h eTcdI YOe KHGJ JLGfS GdJHGjf , GdeJZjQGJ GdeJCNQI RefjG GdeYGOdGJ GdBfjI h WQb JYOjdgG , GdeJZjQGJ GdhgejI h JMdjd OGdI GdGfJGL h JMdjd GdSHHjIs
Keywords: (3GdEMUGA (B- (3GdeYGedGJ GdEQJHGWjI s; (3GdEbJUGO GdJMdjdjs; (3GdEbJUGO GdbjGSjs